Faktor-faktor yang Mempengaruhi Kejadian Tuberkulosis: Sebuah Review - Nur’aini Nur’aini; Suhartono Suhartono; Mursid Raharjo (Poltekkes Kemenkes Yogyakarta, 2021)
Tuberculosis (TB) is still one of the world's public health problems even though TB ??control efforts have been implemented in many countries since 1995. Of all the MDG indicators for TB in Indo-nesia, currently only the target of reducing the incidence rate has been achieved. A bigger and more integrated effort is needed so that Indonesia can achieve the SDG target by 2030. How-ever, the burden of TB in Indonesia is still very high, it is estimated that HIV prevalence among TB patients is 6,2%. The number of TB-RO cases is estimated to be 6,700 cases originating from 1,9% of TB-RO cases from new TB cases and there are 12% TB-RO cases from TB with repeat treatment. The purpose of this study was to analyze the influence of TB risk factors on the incidence of pulmonary TB in Indonesia and to identify the most dominant risk factors. This is a literature review of several journals and books. The risk factors that influence the incidence of pulmonary TB are socio-economic factors, demographic factors, environmental health factors, household energy factors/cooking fuel, TB preventive action factors, smoking habits, contact factors with TB sufferers and symptom factors and treatment history. previous. Meanwhile, envi-ronmental health factors include the house and its environment such as the type of walls, humi-dity, air temperature, type of floor, area of ??ventilation, lighting, and occupancy density.